Design of bifurcation junctions in artificial vascular vessels additively manufactured for skin tissue engineering. (June 2015) - Han, Xiaoxiao; Bibb, Richard; Harris, Russell
Abstract: Construction of an artificial vascular network ready for its additive manufacturing is an important task in tissue engineering. This paper presents a set of simple mathematical algorithms for the computer-aided design of complex three dimensional vascular networks. Firstly various existing mathematical methods from the literature are reviewed and simplified for the convenience of applications in tissue engineering. This leads to a complete and step by step method for the construction of an artificial vascular network. Secondly a systematic parametric study is presented to illustrate how the various parameters in the vascular junction model affect the key factors that have to be controlled when designing the bifurcation junctions of a vascular network. These results are presented as a set of simple design rules and a design map which serve as a convenient guide for tissue engineering researchers when constructing artificial vascular networks. Highlights: Construction of an artificial vascular network ready for its additive manufacturing is an important task in tissue engineering. A set of simple mathematical algorithms for computer-aided design of complex three dimensional vascular networks are provided. A systematic parametric study is presented. A set of simple design rules and a design map which service as a convenient guide for tissue engineering researchers are generated. An example of application and its flowchart are presented.